Development of Teaching Modules Based on Problem-Based Learning to Facilitate Mathematical Problem-Solving Skills - Indra Hayati Putri; Rian Dian Anggraini; Nahor Murani Hutapea (AL-ISHLAH: Jurnal Pendidikan, 2025)
This study addresses the limited availability of effective teaching modules that support the Merdeka curriculum. The objective is to develop a teaching module on linear equations and inequalities with one variable using the Problem-Based Learning (PBL) model, aiming to enhance students’ mathematical problem-solving abilities. The research utilized the 4-D development model (Define, Design, Develop, Disseminate). The teaching module, designed for Phase D, was evaluated for validity and practicality. Validation instruments included expert review sheets assessing identity/general information, core components, and appendices. Practicality was assessed through teacher and student questionnaires. Validation results indicated that the module was highly valid. Average expert ratings were 3.74 for identity/general information, 3.73 for core components, and 3.75 for appendices. The practicality assessment showed high levels of acceptance, with teacher responses averaging 3.62. Student responses in a small group trial averaged 3.61, while those in a large group trial averaged 3.50—both categorized as very practical. The findings demonstrate that the developed module is both valid and practical for use in classroom settings. Its integration of the PBL model supports students' active engagement and enhances their problem-solving skills. The teaching module developed using the PBL approach meets the criteria for both validity and practicality. It serves as an effective instructional tool for teaching linear equations and inequalities in alignment with the Merdeka curriculum.